Psychomotor and Scientific Attitude Assessment to Simple Plane Materials through Application of Direct Instruction Learning Model - Azhar, Azhar (RADINKA JAYA UTAMA PUBLISHER, 2022)
The purpose of this study was to analyze the psychomotor learning outcomes and scientific attitudes of students. This type of research is pre-experimental in the form of one shoot case study. The data analysis technique used is a descriptive analysis by assessing the psychomotor and scientific attitudes of students. The result of this research is that the students' psychomotor absorption ability is classified as good (80.67%). The effectiveness of learning is classified as effective (80.67%). Learning outcomes are classified as complete (88.8%) and classically, psychomotor learning objectives are declared incomplete (63.63%). The scientific attitude of students is classically categorized as high (74.27%). Analysis of psychomotor assessment and scientific attitude can help students achieve the target of completeness that has been set.